Temperature-Dependent Photoluminescence Characteristics of InAs/GaAs Quantum Dots Directly Grown on Si Substrates - 王霆 刘会赞 张建军 (Chinese physics letters, 2016)
The first operation of an electrically pumped 1.3μm InAs/GaAs quantum-dot laser was previously reported epitaxially grown on Si （100） substrate. Here the direct epitaxial growth condition of 1.3μm InAs/OaAs quantum on a Si substrate is further investigated using atomic force microscopy, etch pit density and temperature-dependent photoluminescence （PL） measurements. The PL for Si-based InAs/GaAs quantum dots appears to be very sensitive to the initial OaAs nucleation temperature and thickness with strongest room-temperature emission at 40000 （17Onto nucleation layer thickness）, due to the lower density of defects generated under this growth condition, and stronger carrier confinement within the quantum dots.